A review on integration of carbon fiber and polymer matrix composites in 3D printing technology - Kaptan, Arslan; Kartal, Fuat (International Advanced Researches and Engineering Journal, 2024)
Three-dimensional (3D) printing applications obtained by combining the lightness, high strength, and durability of carbon fiber with polymer matrix composites provide various industrial advantages. These advantages offer new design and production opportunities for automotive, aviation, space, medical devices, and many other industrial fields. This review article discusses material innovations in 3D printing technology with a focus on the integration of carbon fiber and polymer matrix composites. After examining the current state and future potential of 3D printing technology, the properties and advantages of carbon fiber and polymer matrix composites and the difficulties encountered with their integration into the 3D printing process were examined. In conclusion, this review article comprehensively discusses the current status, advantages, challenges, and future directions on the integration of carbon fiber and polymer matrix composites in 3D printing technology. This article can be an important resource for industry professionals and researchers in materials science and engineering.
Keywords: Three-dimensional printing; Additive manufacturing; Polymers; Composite; Carbon fiber